High-intensity endurance training increases nocturnal heart rate variability in sedentary participants - A Nummela; E Hynynen; P Kaikkonen; H Rusko (Termedia Publishing House, 2016)
The effects of endurance training on endurance performance characteristics and cardiac autonomic modulation during night sleep were investigated during two 4-week training periods. After the ﬁrst 4-week training period (3 x 40 min per week, at 75% of HRR) the subjects were divided into HIGH group (n = 7), who performed three high-intensity endurance training sessions per week; and CONTROL group (n = 8) who did not change their training. An incremental treadmill test was performed before and after the two 4-weektraining periods. Furthermore, nocturnal RR-intervals were recorded after each training day. In the second 4-weektraining period HIGH group increased their V0Zmax (P = 0.005) more than CONTROL group. At the same time, nocturnal HR decreased (P = 0.039) and high-frequency power (HFP) increased (P = 0.003) in HIGH group while no changes were observed in CONTROL group. Furthermore, a correlation was observed between the changes in nocturnal HFP and changes in V0Zmax during the second 4-week training period (r = 0.90, P < 0.001). The present study showed that the increased HFP is related to improved VO2max in sedentary subjects suggesting that nocturnal HFP can provide a useful method in monitoring individual responses to endurance training.